Design, synthesis, and biological evaluation of novel fluorinated pyrazole encompassing pyridyl 1,3,4-oxadiazole motifs - Desai, Nisheeth C.; Kotadiya, Ghanshyam M.; Trivedi, Amit R.; Khedkar, Vijay M.; Jha, Prakash C. (Medicinal Chemistry Research, 2016)
A rational approach was adopted for the synthesis of 1-(2-(3-(4-fluorophenyl)-1-phenyl-1H-pyrazol-4-yl)-5-(pyridin-4-yl)-1,3,4-oxadiazol-3(2H)-yl)-3-(aryl)prop-2-en-1-ones (5a-n) using conventional heating as well as microwave irradiation techniques. Compounds 5a-n were tested for their in vitro antimicrobial activity and cytotoxicity. Compounds 5g showed most potent antibacterial activity, while compound 5k emerged as the most effective antifungal agent. The most active compounds 5f, 5g, 5l, and 5m were also screened against methicillin-resistant Staphylococcus aureus. Among these compounds, 5g and 5m inhibited the growth against MRSA at low level of cytotoxicity. A binary quantitative structure-activity relationship based recursive partitioning model was developed to probe the physico-chemical properties influencing the structure-activity relationship for this class of molecules, which was used to correctly classify active and inactive compounds.